When shah went weird - Oldfield, Jenny; Farrow, Martina (Hodder Children's Books London, 2002)
Fun, quirky, contemporary diary series by a million selling author. In the last story, Tiff's life is finally going well for a change - until her friend Shah starts acting really weird ... Read on - if you can get hold of a copy!